KREATIVITAS DIDIK BAMBANG WAHYUDI DALAM KARYA TARI ANOMAN CAKIL - Denny Rostyana Putri; Karyono Karyono (Greget, 2020)
This thesis is titled by the Creativity of Didik Bambang Wahyudi in Anoman Cakil dance to uncover the creativity of Didik Bambang Wahyudi by describing and explaining: (1) The form of Anoman Cakil dance and (2) Didik Bambang Wahyudi’s creativity in the works of Anoman Cakil dance. Both issues were examined using the concept of the show form by Maryono which reveals verbal and non-verbal components. To uncover the creativity of Didik Bambang Wahyudi in the work of Anoman Cakil dance is using the theory of Rhodes cited by Utami Munandar that creativity there are four elements in it, namely person, press, proscess and product. Anoman Cakil dance composed by Didik Bambang Wahyudi told about the battle between two characters that have different character of Anoman and Cakil. Anoman Cakil dance is a dance work born from the interpretation of Didik Bambang Wahyudi. Harmony between the person and the creative process, as well as the ability to implement a story where Anoman essentially never met Cakil, but it is not impossible for Anoman to meet Cakil on a journey.Keywords: creativity, form, Anoman Cakil dance.